2016
DOI: 10.1016/j.dnarep.2015.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Endonuclease activities of MutLα and its homologs in DNA mismatch repair

Abstract: MutLα is a key component of the DNA mismatch repair system in eukaryotes. The DNA mismatch repair system has several genetic stabilization functions. Of these functions, DNA mismatch repair is the major one. The loss of MutLα abolishes DNA mismatch repair, thereby predisposing humans to cancer. MutLα has an endonuclease activity that is required for DNA mismatch repair. The endonuclease activity of MutLα depends on the DQHA(X)2E(X)4E motif which is a part of the active site of the nuclease. This motif is also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 153 publications
(263 reference statements)
0
57
0
1
Order By: Relevance
“…5Bc). A second model posits that assembly of the MutL␣ complex is an early event and that, once formed, the complex slides along DNA and contacts mismatch-activated MutS␣, whereupon the MutL␣ endonuclease activity is activated (54). The key difference is that MutL␣ can independently slide along the DNA contour in the second model.…”
Section: Discussionmentioning
confidence: 99%
“…5Bc). A second model posits that assembly of the MutL␣ complex is an early event and that, once formed, the complex slides along DNA and contacts mismatch-activated MutS␣, whereupon the MutL␣ endonuclease activity is activated (54). The key difference is that MutL␣ can independently slide along the DNA contour in the second model.…”
Section: Discussionmentioning
confidence: 99%
“…Crystallographic analyses on the C-terminal domain (CTD) of eukaryotic and bacterial MutL endonuclease have shown that the domain is composed of regulatory and dimerization subdomains (11, 26 -28). The dimerization subdomain contains the metal-binding site essential for the endonuclease activity (29), in which two zinc ions are coordinated by the residues from highly conserved motifs: DQHAX 2 EX 4 E, ACR, and CPHGRP (11,15,26,30). These motifs are conserved in MutL from the majority of organisms except for limited species in ␥-proteobacteria (12, 15, 16, 19 -21, 31).…”
Section: Dna Mismatch Repair (Mmr)mentioning
confidence: 99%
“…The multifunctional MMR system plays a major role in maintaining genome integrity in bacteria and eukaryotes (1)(2)(3)(5)(6)(7)(8). The genetic stability engendered by the MMR system is required for the suppression of both sporadic and inherited cancers in humans (4).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic stabilization provided by the MMR system suppresses both sporadic and inherited cancers (4). The MMR system has multiple functions that are involved in the genome maintenance (1)(2)(3)(5)(6)(7)(8). Among these functions MMR is the strongest contributor to the suppression of spontaneous mutation rates.…”
mentioning
confidence: 99%
See 1 more Smart Citation